2023
DOI: 10.1051/0004-6361/202244786
|View full text |Cite
|
Sign up to set email alerts
|

The outburst of the changing-look AGN IRAS 23226-3843 in 2019

Abstract: Aims. IRAS 23226-3843 has previously been classified as a changing-look active galactic nucleus (AGN) based on observations taken in the 1990s in comparison to X-ray data (Swift, XMM-Newton, and NuSTAR) and optical spectra taken after a very strong X-ray decline in 2017. In 2019, Swift observations revealed a strong rebrightening in X-ray and UV fluxes. We aimed to study this outburst in greater detail. Methods. We took follow-up Swift, XMM-Newton, and NuSTAR observations of IRAS 23226-3843 together with optic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 100 publications
1
8
0
Order By: Relevance
“…± 10. km s −1 of the stars in the bulge of NGC 1566 17,18 . We confirm this total central black hole mass of 5 × 10 6 M ⊙ based on CaII triplet observations in NGC 1566 19 .…”
supporting
confidence: 85%
See 3 more Smart Citations
“…± 10. km s −1 of the stars in the bulge of NGC 1566 17,18 . We confirm this total central black hole mass of 5 × 10 6 M ⊙ based on CaII triplet observations in NGC 1566 19 .…”
supporting
confidence: 85%
“…Further Swift observations 22 from July 10, 17, 24, and 31 verified the high X-ray and UV flux states, but indicated a decrease with respect to the observation taken on July 10. Follow-up observations in the X-ray with Swift and XMM 23 as well as in the optical 24,25,19 also confirm a decline in the optical, UV and X-ray emission over the following two years and in late 2023 NGC 1566 is still found in a low state in all Swift bands 26 The general shape of the outburst light curve looks surprisingly symmetrical with respect to its highest flux peak in mid 2018 -with additional smaller peaks superimposed on either wing.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…The optical spectrum of this AGN has an asymmetric broad H α emission line as well as a broad double-peaked H β emission line. In addition, the source also has narrow emission lines like Kollatschny et al (2023) reported that the optical continuum and the Balmer line intensities showed drastic differences when the spectra were compared between the years 1999 and 2017. The double-peaked emission line is from the underlying accretion disk in this source.…”
Section: A Changing-look Agnmentioning
confidence: 98%